Normative speech recognition threshold in noise (SRTn) for Malay matrix sentence test (MMST) in open-set format - Mustafar Ramdzuan, Lydia Farhana; Jamaluddin, Saiful Adli; O'Beirne, Greg A. (Kulliyyah of Allied Health Sciences, IIUM, 2018)
Speech perception ability in noise is a realistic key indicator of a person’s potential to communicate in real-world situations. The Malay Matrix Sentence Test (MMST) is able to provide information about a listener’s speech perception ability in noise. It can also be implemented in either open or closed-set test format. The main purpose of this study was to obtain normative speech recognition threshold in noise (SRTn) for MMST in the open-set test format.